Integrated stress response control of granulosa cell translation and proliferation during normal ovarian follicle development. (26th July 2021) - Llerena Cari, Evelyn; Hagen-Lillevik, Synneva; Giornazi, Asma; Post, Miriam; Komar, Anton A; Appiah, Leslie; Bitler, Benjamin; Polotsky, Alex J; Santoro, Nanette; Kieft, Jeffrey; Lai, Kent; Johnson, Joshua
Abstract: Mechanisms that directly control mammalian ovarian primordial follicle (PF) growth activation and the selection of individual follicles for survival are largely unknown. Follicle cells produce factors that can act as potent inducers of cellular stress during normal function. Consistent with this, we show here that normal, untreated ovarian cells, including pre-granulosa cells of dormant PFs, express phenotype and protein markers of the activated integrated stress response (ISR), including stress-specific protein translation (phospho-Serine 51 eukaryotic initiation factor 2α ; P-EIF2α ), active DNA damage checkpoints, and cell-cycle arrest. We further demonstrate that mRNAs upregulated in primary (growing) follicles versus arrested PFs mostly include stress-responsive upstream open reading frames (uORFs). Treatment of a granulosa cell (GC) line with the PF growth trigger tumor necrosis factor alpha results in the upregulation of a 'stress-dependent' translation profile. This includes further elevated P-eIF2α and a shift of uORF-containing mRNAs to polysomes. Because the active ISR corresponds to slow follicle growth and PF arrest, we propose that repair and abrogation of ISR checkpoints (e.g. checkpoint recovery) drives the GC cell cycle and PF growth activation (PFGA). If cellular stress is elevated beyond a threshold(s) or, if damage occurs that cannot be repaired, cell and follicle death ensue, consistent with physiological atresia. These data suggest an intrinsic quality control mechanism for immature and growing follicles, where PFGA and subsequent follicle growth and survival depend causally upon ISR resolution, including DNA repair and thus the proof of genomic integrity.